Staphyloxanthin and Meropenem Effects on Some Capsular Genes Expressions of Klebsiella pneumoniae Isolated from UTIs - Raja, Noor Al-huda Adel; Alattar, Nagham Shakir (Iraqi Journal of Science, 2024)
Klebsiella pneumoniae has become one of the most common etiologic agents in the context of recurrent UTI. Capsule is the earliest recognized factor determining bacterial pathogenicity. This study aimed to test the effects of staphyloxanthin, meropenem and a combination of them on capsule genes of Klebsiella pneumoniae. Eighty-eight gram negative bacterial isolates were collected from 150 urine specimens between September and November of 2022.after cultivation on MacConkey agar medium. Oxidase (negative) and catalase (positive) tests were performed. In addition, all isolates were found to be non-motile when their motility was further examined. The results presented that 77 (51.3%) could ferment lactose (lactose fermenter), while 30 isolates (20%) of them were confirmed as K. pneumonia. The antibiotics sensitivity test of (30) K. pneumoniae revealed that 28 (93%) of isolates were sensitive to meropenem, and about 20 (67%), 16 (53%), 8 (27%), 7 (23%), 5 (17%) and 4 (13%) were sensitive toward amikacin, ciprofloxacin, trimethoprim, cefepime, tetracycline and Augmentin respectively. S. aureus (producers of staphyloxanthin) isolates were taken; the staphyloxanthin pigment was extracted, purified by Millipore filter (0.22 mm). Conventional PCR results revealed the presence of galF gene (141 bp) in all eight tested isolates (100%). In addition, the wzi gene (177bp) was found in seven isolates (87.5%). According to the quantitative real-time PCR results, most treatments resulted in downregulation of galF and wzi genes expression, whereas some treatments resulted in upregulation.